Knowledge management and growth in manufacturing SMEs from Aguascalientes (Mexico) - Maldonado Guzman, Gonzalo; Martínez Serna, María Del Carmen; García Ramírez, Ricardo (Cuadernos de Administración, 2012)
Within a constantly changing market and an uncertain environment for business, knowledge has become one of the valued intangible resources appreciated by firms. For this, more and more firms are applying managerial strategies to promote the development of knowledge, both tacit and implicit, in such a way that allows them to achieve expected success. Also, an important number of companies, mainly small and medium-sized enterprises, are getting involved with knowledge management as part of their daily activities, seeking to improve higher growth. Thus, the value of knowledge is increasing, to such a measure that firms are hiring the most brilliant minds in each specialty. In this sense, this paper aims to analyze the relationship between knowledge management and growth, starting from a sample of 125 SMEs from the State of Aguascalientes (Mexico). The results obtained show that knowledge management has positive and significant effects on the growth of SMEs, which can constitute a competitive advantage